«A CHURCH-COFFIN WILL FALL TO PIECES. AND UKRAINE WILL GET UP FROM UNDER IT» (A few strokes to the analysis of poem-mystery of T. Shevchenko the «Large cellar») - Slonovsca, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the poem «Velykyi Liokh» by Taras Shevchenko. Special attention is focused on archetypical images and images-symbols.